Improvements of microstructure and mechanical properties of wire-arc directed energy deposition 2024 aluminum alloy after adding TiC nanoparticles - Xiaoyu Cai; Dongyuan Liu; Bolun Dong; Sanbao Lin (Virtual and Physical Prototyping)
To address issues such as grain coarsening, high porosity, and poor mechanical properties that commonly occur in high-strength 2024 aluminum alloy (AA2024) during directed energy deposition using an electric arc (DED-A), this work proposes a strategy of adding TiC nanoparticles to the AA2024 welding wire for DED-A and reveals the mechanism of TiC nanoparticles modification. AA2024 and TiCP/AA2024 composite were fabricated by DED-A. By adding TiC nanoparticles, the average grain diameter of the as-deposited TiCP/AA2024 composites considerably decreases from 65.4 μm to 16.4 μm. TiC nanoparticles refine the grains by promoting nucleation and inhibiting grain growth. Correspondingly, the mechanical properties of the as-deposited TiCP/AA2024 have been significantly improved: the horizontal tensile strength, yield strength, and elongation are 304 , 174 MPa, and 9.5%, respectively, which represent increases of 75%, 70%, and 164% compared to AA2024, and the tensile strength, yield strength, and elongation in the vertical direction are 287 MPa, 165 MPa, and 9.9%, respectively, with no significant anisotropy observed.